Rethinking ecoanxiety through environmental moral distress: an ethics reflection - Nicola Banwell; Nadja Eggert (The Journal of Climate Change and Health, 2024)
Humanity is currently confronted with simultaneous complex environmental crises of unprecedented scale. These include, but are not limited to, the ongoing sixth mass extinction and the depletion of biodiversity, and ongoing anthropogenic greenhouse gas emissions which are causing changes in the climate that humanity has never before witnessed. As these ecological crises continue to progress, there is increasing recognition of the impact this has on mental health. Within this context, the notion of ecoanxiety has gained traction, primarily from the perspective of psychology, with the view to elevate suffering. However, in our view, the risk of considering ecoanxiety, and other ecological emotions, solely from a medicalized perspective as a mental disorder is that it places too much responsibility on individuals, decontextualizes ecological emotions from their social and political settings, and detaches these emotions from their ethical and moral dimensions. This article proposes to reconsider ecological emotions from the perspective of moral distress. Environmental moral distress resituates ecological emotions within their social and political contexts, and sheds light on their entanglement with ethical realms that medicalized conceptions of ecoanxiety fail to recognize. We argue that responding to environmental moral distress requires a shift to an ethics of care and ecofeminist paradigm which enables us to consider ecological emotions as contextualized indicators of the experience of morally questionable actions. This approach opens the door to collective responses aiming to empower and build moral agency in the face of the shared moral and political struggles which characterize the ecological crisis.